A window on Williamsburg - Lewis, Taylor Biggs; Walklet, John J., 1922-; Colonial Williamsburg, inc. (Williamsburg, Va. : Colonial Williamsburg; distributed by Holt, Rinehart and Winston, New York, 1966)
Color photographs with brief captions highlight the restoration of eighteenth-century Colonial Williamsburg, both indoors and out, and during all seasons.
Keywords: Williamsburg (Va.) -- Pictorial works; Williamsburg (Va.) -- Pictorial works